Ketahan Keluarga Dihubungkan Dengan Wanita Karir Di Desa Mekaraja, Kecamatan Sukaraja, Kabupaten Tasikmalaya - Ifan Ardiansyah; Shindu Irwansyah; Fahmi Fatwa Rosyadi Satria Hamdani (Bandung Conference Series: Islamic Family Law, 2024)
Abstract. After marriage, men and women are assigned duties and responsibilities that align with their respective roles. These responsibilities are not easily fulfilled. One of the central issues and challenges in marriage is the failure to execute the functions and duties associated with these responsibilities by both parties (husband and wife), which can lead to the goals of the marriage not being realized. This study addresses the issue of the responsibilities of husbands and wives within the framework of family law, and provides a legal analysis of these responsibilities from the perspective of Islamic family law. The research employs a qualitative method with a descriptive analysis approach. The data sources used in this study include both qualitative and quantitative data, with primary and secondary sources. The research utilizes an empirical juridical approach to address the issues, and data collection was conducted through library research.The findings of the study highlight the responsibilities of husbands and wives as outlined in family law, which are informed by the Al-Qur'an, Hadith, the Marriage Law, and the Compilation of Islamic Law. Specifically, the study identifies the responsibilities of husbands and wives and provides a legal analysis of these responsibilities within the context of Islamic family law, drawing from the Al-Qur'an, Hadith, the Marriage Law, and the Compilation of Islamic Law. Keywords: Living, Islamic Family Law, Responsibility, Husband and Wife, family resilience Abstrak. Setelah perkawinan, laki-laki dan perempuan mendapatkan tugas dan tanggung jawab yang sesuai dengan kodrat masing-masing. Tanggung jawab ini tidaklah mudah untuk dilaksanakan. Salah satu masalah utama dan hambatan dalam perkawinan adalah ketidakmampuan suami dan istri untuk menjalankan fungsi dan tanggung jawab mereka dalam perkawinan. Penelitian ini berfokus pada tanggung jawab suami dan istri dalam hukum keluarga serta bagaimana peran wanita karir dianalisis dari perspektif Hukum Islam dalam kaitannya dengan ketahanan keluarga. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif analisis, memanfaatkan data primer dan sekunder sebagai sumber data kualitatif. Masalah dianalisis melalui pendekatan yuridis empiris dan teknik analisis sampling. Pengumpulan data dilakukan melalui studi pustaka (library research). Hasil penelitian menunjukkan bahwa peran wanita karir terkait dengan ketahanan keluarga dari perspektif Hukum Islam dapat dilihat dalam Al-Qur’an dan Hadits, serta didukung oleh Undang-Undang Perkawinan dan Kompilasi Hukum Islam. Berdasarkan analisis hukum ini, tanggung jawab suami dan istri dalam hukum keluarga Islam diatur oleh Al-Qur’an, Hadits, Undang-Undang Perkawinan, dan Kompilasi Hukum Islam. Kata Kunci: Nafkah, Hukum Keluarga Islam, Tanggung Jawab, Suami dan Istri, Ketahanan Keluarga